P630 Non infectious complications related to central catheter in neonates (a study of 8 cases). (June 2019) - Charfi, Manel; Hamad, Amel Ben; Amar, Sahar Ben; Regaieg, Chiraz; Bouraoui, Amira; Regaieg, Ridha; Hmida, Nedia; Thabet, Afef Ben; Abdellatif, Gargouri
Abstract : Introduction: The use of central catheters in the neonatal period is essential for the management of neonates with vital distress or premature newborns. Nevertheless it can be associated to serious complications specially related to leakage of parenteral nutrition. Methods: It's a retrospective study of all cases of non infectious complication related to central catheter registered in the neonatal intensive care unit of Sfax between 2012 and 2018. Results: We registered 5 cases of pericardial effusion, one case of pleural effusion, one case of ascites and one case of pneumopericardium. All newborns were premature (29 to 33 weeks of amenorrhea). Five patients had epicutaneo-cave catheters, two patients had umbilical venous catheters and one had broviac catheter. The catheter position was intracardiac in all cases. The incident occurred in an average of 2.75 days after the catheter insertion (1to 6 days). Clinical manifestations were no specific miming sepsis in almost all cases. Hemodynamic disorders with tachycardia, tachypnea and skin mottling were noticed in 4 cases of pericardial effusion. Three preterm newborns with tamponade presented moreover severe apnea. The newborn with ascites presented abdominal distension and tachypnea. Diagnosis was made by ultrasound exam in all cases related to leakage of parenteral nutrition. For the case of pneumopericardium diagnosis was made on chest radiography. Management consistent on oxygen administration associated to hemodynamic support all cases. An ultrasound-guide pericardium puncture was performed in four cases of pericardial effusion. The catheter was removed in five cases and repositioned in three cases. Outcome was favorable four all newborns. Conclusion: Clinician should be aware of the risk of leakage of parenteral nutrition. Thus every neonate with central catheter must be monitored and the extracardiac position of the catheter must be systematically verified.